FUNKCIYALÍQ TEŃLEMELERDI SHESHIWDIŃ GEYPARA USÍLLARÍ - Saparov, Z.B.; Kalbaev, S.N. (SCIENCE and SOCIETY, 2019)
Functional equations and methods of their solution are not studied in the school course of Mathematics, such equations are mainly found in the tasks of the Olympiad in Mathematics. The article presents some methods for solving such equations.